Study of the earthquakes source parameters, site response, and path attenuation using P and S-waves spectral inversion, Aswan region, south Egypt - Saadalla Hamada; Qaysi Saleh; Hayashida Takumi; Hamada Mona (Open Geosciences)
Aswan broadband seismic network with highly sensitive sensors and good station coverage gave the opportunity to study the seismicity distribution, focal depth, the fault plane solution, the attenuation of seismic wave, the station sites response, and the source spectra of Aswan earthquakes with magnitude (ML)\left(M_{{\rm{L}}}) between 0.8 and 4.2 recorded from 2010 to 2023 comprehensively. Preliminary analysis of Aswan seismicity during the studied period indicated strike-slip mechanism with minor normal sense is dominant, relatively deep seismicity concentrated beneath Gabal Marawa, whereas shallow seismicity are dominant features of other zones in Aswan region, and the epicenter distribution characterized by cluster forms, frequently occurred earthquakes in the same patches, and concentrated in the intersection area between the two orthogonal fault systems. A generalized inversion technique (GIT) constrained by reference site is applied to separate the path effect, the recording station sites responses and the source spectra from the observed P- and S-waves by means of iterative least square analysis. The separated station sites effects show similar trend using P- and S-waves, with flat curve in the low frequency band from 0.8 to 8 Hz, whereas the station sites responses have peak amplitudes deviated from 4 to 10 in the higher frequencies. The attenuation through propagation is evaluated and empirically formulated Qp=(133±2.09)f (0.54±0.034)Q_{{\rm{p}}}\left=(133\left± 2.09){{f}}^{(0.54\left± 0.034)} and Qs=(91±1.9)f (0.8±0.045)Q_{{\rm{s}}}\left=(91\left± 1.9){{f}}^{(0.8\left± 0.045)} for P- and S-waves, respectively. The given attenuation fitting relation for P- and S-waves indicated the frequency dependence of seismic wave’s attenuation in the study area. The low-quality factor Q0Q_{0} at reference frequency (f0{f}_{0}) pointed that Aswan region is an active region. Furthermore, the low value of Q0Q_{0} would indicate that the medium is complex and highly heterogeneous. The third element separated from the observed seismogram is the displacement source spectra which modulated using Brune’s omega square. The advanced earthquake’s source parameters (seismic moment, corner frequency, moment magnitude, and static stress drop and source radius) and its scaling relations are computed using the converted windows of P- and S-waves. The displacement source spectra for seismic events with ML<3M_{{\rm{L}}}\lt 3 decayed rapidly at 20 Hz in the frequency bands of 0.8–50 Hz, whereas it is decreased rapidly at 10 Hz for seismic events with magnitude 3≤ML<4.23\le {M}_{{\rm{L}}}\lt 4.2. The seismic moment, the source radius, and the corner frequency range from 9.50 × 1016 to 2.18 × 1021 dyne-cm, from 28 to 190 m, and from 4 to 36 HZ, respectively. The observed stress drops for the studied earthquakes vary from 0.01 to 12 Mpa, whereas the stress drop for S-portion ∆σS{\triangle σ }^{{\rm{S}}} ranged from 0.03 to 22 Mpa. The low stress drop values may reflect that reservoir–triggered earthquakes may have a lower stress drop than tectonic and crustal ones.